Il trattamento dei disturbi psicotici con olanzapina, risperidone e neurolettici tipici: una valutazione comparativa di costo/efficacia in una realtà psichiatrica locale - Filippelli, Egidio; Biricolti, Giovanni; Scarano, Cinzia; Russo, Federico; Luciano, Lucio (Farmeconomia. Health Economics and Therapeutic Pathways, 2005)
BACKGROUND: Several clinical trials demonstrated that atypical antipsychotics are more effective but also more expensive (as drug cost) compared with the typical neuroleptics by treating psychotic disorders. The present study aimed to evaluate this result using an observational approach which better reflects the real clinical practice. OBJECTIVE: To evaluate clinical effectiveness (including work and social functioning) and overall direct costs in a group of patients affected by psychotic disorders (schizophrenia and bipolar) and treated with typical and atypical (olanzapine and risperidone) antipsychotics. METHODS: With a multicentre observational design - two years long - 89 patients (in charge by Psychiatric Centers of Regione Campania - Italy) were assessed using CGI (Clinical Global Impression) and GAF (Global Assessment of Functioning) scales. Moreover economic data were collected with reference to pharmacological and non-pharmacological (hospitalization, medical/nurse visits, etc.) resources consumption. The pharmacoeconomic analysis were conducted choosing the perspective of the local Psychiatric Services for costs attribution. RESULTS: Considering the treatment outcomes, the use of the atypical drugs provided better performances with reference to the patients quality of life. The results in terms of work and social functioning indicated an advantage in the olanzapine group of patients. Overall direct costs of treatment (drugs and healthcare resources) didn’t generate significant differences among the groups of therapy despite the pharmacological cost evidentiated an economic advantage (p